Central African Republic : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document. (IMF Staff Country Reports; Country Report ;, 2008)
This paper presents an assessment of the Central African Republic's (C.A.R) qualifications for assistance under the Enhanced HIPC Initiative. Stronger policy implementation has helped the economic growth of the C.A.R. under the Poverty Reduction and Growth Facility (PRGF) arrangement. Directors stressed the need for fiscal consolidation supported by policies and implementation of more structural reforms to meet the challenges. A sensitivity analysis of the C.A.R.'s projected external debt burden highlights the need for economic reforms to diversify and enhance export performance and for sustained foreign assistance on favorable terms to avoid the risk of renewed debt distress.